2014
DOI: 10.1136/bmjopen-2014-005399
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of liver cancer: an update meta-analysis

Abstract: ObjectiveStatins are commonly prescribed cholesterol-lowering drugs. Preclinical studies suggest that statins may possess cancer preventive properties. The primary objective of this meta-analysis was to determine the association between statin use and risk of liver cancer.DesignMeta-analysis.SettingInternational.ParticipantsA comprehensive literature search of PubMed, BIOSIS Previews, Web of Science, EMBASE, EBSCO and Cochrane Library was conducted through March 2014. The effect estimate was reported as pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 51 publications
6
54
0
Order By: Relevance
“…Moreover, in human statins treatments modify in vivo immune cells response by decreasing inflammatory cytokines concentration, increasing CD8+ T cells frequency and T lymphocytes activation . Additionally, retrospective studies have shown that statins can also have a protective effect against the development of cancers, particularly melanomas and liver cancers . Since 16 years, different farnesyl transferase inhibitors (FTI) have been evaluated during clinical trials demonstrating a limited anti‐tumor activity in hematologic cancers and no therapeutic efficiency in solid tumors treatment .…”
Section: Statins and Pharmacological Inhibitors Of Rho Gtpases Prenylmentioning
confidence: 99%
“…Moreover, in human statins treatments modify in vivo immune cells response by decreasing inflammatory cytokines concentration, increasing CD8+ T cells frequency and T lymphocytes activation . Additionally, retrospective studies have shown that statins can also have a protective effect against the development of cancers, particularly melanomas and liver cancers . Since 16 years, different farnesyl transferase inhibitors (FTI) have been evaluated during clinical trials demonstrating a limited anti‐tumor activity in hematologic cancers and no therapeutic efficiency in solid tumors treatment .…”
Section: Statins and Pharmacological Inhibitors Of Rho Gtpases Prenylmentioning
confidence: 99%
“…Data safety analyses of early randomized controlled trials of statins revealed an inverse association between statin use and cancer incidence . Preclinical studies have demonstrated growth‐suppressive effects on various tumors, and epidemiologic studies have shown inverse associations with overall cancer risk and the risk of other gastrointestinal cancers, including esophageal, colorectal, and liver cancer …”
Section: Introductionmentioning
confidence: 99%
“…6 Preclinical studies have demonstrated growth-suppressive effects on various tumors, and epidemiologic studies have shown inverse associations with overall cancer risk 7,8 and the risk of other gastrointestinal cancers, including esophageal, 9 colorectal, 10 and liver cancer. 11 Previous studies of statin use and PC risk are inconsistent. Some randomized controlled trials and cohorts were underpowered, [12][13][14][15][16][17] and among nontrial studies, 7,[18][19][20][21][22][23][24][25][26] few examined associations by sex with the exception of a large study of predominantly male veterans 26 and a UK study 19 in which inverse relationships were observed only in men and male smokers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Statins have been proposed to be beneficial in cancer prevention, including melanoma and cancer of the colon, breast and prostate as well as HCC . Statins are selectively distributed in the liver as target organ, and the majority of their beneficial effects appear to be mediated primarily by modulating lipid metabolism, mainly in the liver .…”
mentioning
confidence: 99%